A Computer-Aided Assessment and Evaluation System for Modern Apprenticeship of Accounting Class On-the-Job Training. (30th July 2022) - Sun, LinLin; Liu, ChunChao; Lin, MaoNian; Zhou, Ying
Abstract : With China's economy and the accelerated pace of globalization, the accounting environment is constantly changing, some accounting laws and regulations are constantly being revised or promulgated, and the accounting system and system are gradually being improved. At the same time, breach of trust in economic activities and violation of financial laws and regulations are common, making the accounting environment more complex. All these have put forward higher requirements for accounting practitioners, which require accounting personnel to receive systematic and professional accounting professional training. Therefore, it is very important for the construction of the assessment and evaluation system for accounting internship. Based on this paper, we study the construction of the computer-aided implementation of the assessment and evaluation system of accounting internship for modern apprenticeship in order to improve the practical and effective help for the employment of accounting students.